2010
DOI: 10.1523/jneurosci.4088-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Inflammasome Sensor, NLRP3, Regulates CNS Inflammation and Demyelination via Caspase-1 and Interleukin-18

Abstract: Inflammation is increasingly recognized as an important contributor to a host of CNS disorders; however, its regulation in the brain is not well delineated. Nucleotide-binding domain, leucine-rich repeat, pyrin domain containing 3 (NLRP3) is a key component of the inflammasome complex, which also includes ASC (apoptotic speck-containing protein with a card) and procaspase-1. Inflammasome formation can be triggered by membrane P2X 7 R engagement leading to cleavage-induced maturation of caspase-1 and interleuki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
194
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(204 citation statements)
references
References 70 publications
10
194
0
Order By: Relevance
“…This study and previous ones (6,7,13) showed that Nlrp3 −/− mice are resistant to the development of EAE, suggesting the association of the NLRP3 inflammasome with EAE development. We also showed that Asc −/− mice were resistant to EAE as Nlrp3 −/− mice.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…This study and previous ones (6,7,13) showed that Nlrp3 −/− mice are resistant to the development of EAE, suggesting the association of the NLRP3 inflammasome with EAE development. We also showed that Asc −/− mice were resistant to EAE as Nlrp3 −/− mice.…”
Section: Discussionsupporting
confidence: 78%
“…Because it is not clear how the NLRP3 inflammasome enhances EAE, we sought to elucidate the mechanism in this study. Currently, the attenuated Th17 cell responses are suggested to be a major underlying mechanism for the resistance of knockout mice to EAE (13,14). Indeed, a number of studies demonstrated the critical role of Th17 responses in EAE development and the promotion of Th17 cell generation by IL-1β.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, MLKL-mediated activation of IL-1β has been reported to cause inflammation mediated tissue damage in a model of Staphylococcus aureus infection (43). In addition, there are a growing number of studies that have separately implicated necroptosis or NLRP3 in driving pathology of atherosclerosis (44)(45)(46), multiple sclerosis (47)(48)(49), and ischemia-reperfusion injury of the heart (50, 51) and brain (52)(53)(54). Indeed, in models of kidney ischemiareperfusion injury, both MLKL (42) and NLRP3 (55) deficiency are protective.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high cathepsin B activity was detected in CSF samples from patients with neuroinflammatory diseases such as multiple sclerosis (62). Inflammasome activation plays an important role in the three diseases listed above by exacerbating brain inflammation (54,63,64). Therefore, it is conceivable that cathepsin B release and activation may represent a more widespread mechanism for the propagation of inflammasome-dependent immune responses in the brain.…”
Section: Discussionmentioning
confidence: 99%